2000
DOI: 10.1016/s0002-9440(10)65048-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Modification of MLH1 Accounts for a Major Share of Microsatellite-Unstable Colorectal Cancers

Abstract: Microsatellite instability (MSI) is a hallmark of hereditary nonpolyposis colorectal cancer, and in these patients, results from inherited defects in DNA mismatch repair genes, mostly MSH2 and MLH1. MSI also occurs in 15% of sporadic colorectal cancers, but in these tumors, its basis is less well characterized. We investigated 46 sporadic MSI+ colorectal cancers for changes in MSH2 and MLH1 protein expression, followed by the analysis of somatic mutation, loss of heterozygosity (LOH), and promoter hypermethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
168
1
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(191 citation statements)
references
References 21 publications
(36 reference statements)
16
168
1
6
Order By: Relevance
“…MLH1 (MutL homolog 1) is the most important susceptibility gene for HNPCC (Peltomaki and Vasen, 2004) and also accounts for a major share of sporadic colorectal cancers (CRC) with microsatellite instability (MSI) (Kuismanen et al, 2000). In HNPCCrelated CRCs, the residual wild-type (wt) allele is often silenced by loss of heterozygosity (LOH) (Tannergard et al, 1997;Kuismanen et al, 2000;Potocnik et al, 2001;Yuen et al, 2002), whereas (biallelic) methylation of the MLH1 promoter primarily underlies sporadic microsatellite-unstable CRCs (Cunningham et al, 1998;Veigl et al, 1998;Kuismanen et al, 2000). Considerably less data are available on the mechanisms of inactivation of the wt allele in HNPCC spectrum tumors other than CRC, notably endometrial cancer (EC) that is the most common extracolonic malignancy in HNPCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLH1 (MutL homolog 1) is the most important susceptibility gene for HNPCC (Peltomaki and Vasen, 2004) and also accounts for a major share of sporadic colorectal cancers (CRC) with microsatellite instability (MSI) (Kuismanen et al, 2000). In HNPCCrelated CRCs, the residual wild-type (wt) allele is often silenced by loss of heterozygosity (LOH) (Tannergard et al, 1997;Kuismanen et al, 2000;Potocnik et al, 2001;Yuen et al, 2002), whereas (biallelic) methylation of the MLH1 promoter primarily underlies sporadic microsatellite-unstable CRCs (Cunningham et al, 1998;Veigl et al, 1998;Kuismanen et al, 2000). Considerably less data are available on the mechanisms of inactivation of the wt allele in HNPCC spectrum tumors other than CRC, notably endometrial cancer (EC) that is the most common extracolonic malignancy in HNPCC.…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic EC resembles sporadic CRC, in that MLH1 promoter methylation appears to be the primary mechanism of MSI (Esteller et al, 1998;Simpkins et al, 1999). In general, somatic point mutations rarely explain MMR gene inactivation in CRC (Tannergard et al, 1997;Kuismanen et al, 2000;Potocnik et al, 2001;Yuen et al, 2002) or EC (Chadwick et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Somatic mutations as second hits have been found in both MLH1-and MSH2-deficient tumors, albeit at low frequencies Konishi et al, 1996;Lu et al, 1996;Cunningham et al, 2001). MLH1 promoter hypermethylation has been detected in 17-46% of the HNPCC tumors (Cunningham et al, 1998;Herman et al, 1998;Kuismanen et al, 2000;Potocnik et al, 2001). Loss of the wild-type allele in HNPCC tumors was proposed by Hemminki et al (1994) and it has been found to be the major mechanism for somatic second hits in most of the studies.…”
mentioning
confidence: 99%
“…Loss of the wild-type allele in HNPCC tumors was proposed by Hemminki et al (1994) and it has been found to be the major mechanism for somatic second hits in most of the studies. Frequency of LOH in published studies varies between 33 and 86% (Hemminki et al, 1994;Lu et al, 1996;Tannerga˚rd et al, 1997;Kuismanen et al, 2000;Potocnik et al, 2001;Yuen et al, 2002), although the lost allele has not always been specified. In contrast, sporadic MMR-deficient tumors are most commonly due to bi-allelic inactivation of MLH1 by promoter hypermethylation, and these tumors rarely show LOH or somatic mutations in MLH1 (Kane et al, 1997;Cunningham et al, 1998;Herman et al, 1998;Veigl et al, 1998;Wheeler et al, 1999;Kuismanen et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation